Multiobjective Optimization Design and Experimental Investigation on the Axial Flow Pump with Orthogonal Test Approach - Yuquan Zhang; Yanhe Xu; Yuan Zheng; E. Fernandez-Rodriguez; Aoran Sun; Chunxia Yang; Jue Wang (Complexity)
A multiobjective optimization technique based on the computational fluid dynamics (CFD) simulations and the orthogonal test is proposed to reduce the pressure pulsation in this paper. Three levels of four well-known performance factors L9 (34) were considered in the orthogonal test scheme: the number of blades, the blade setting angle, the hub ratio, and the distance between the blade and the guide vane. The evaluation indexes corresponded to the head, efficiency, shaft power, and pressure pulsation, respectively. An optimal configuration A2B1C2D3 was obtained by comprehensive frequency analysis method, after intuitive and range analysis. In comparison with the nonoptimized model, the new design’s head and efficiency increased by 17.8% and 4.26%, whilst the shaft power and the pressure pulsation coefficient reduced by 1.22% and 11%, respectively. Experiments conducted on the optimized pump were consistent with the CFD model. Six different rotational speed conditions in the optimal operating points were numerically calculated in order to explore the internal hydraulic characteristics of the optimized axial flow pump. It is verified that the comprehensive frequency analysis method based on the orthogonal test approach is effective for the multiobjective optimization of the axial flow pump.